Fertilidad de Typic Dystrandepts de Costa Rica. I. Metodología, acidez y cationes (Ca, Mg, K, Fe, Mn, Zn, Cu) - Bertsch, F; Cordero, A; Alvarado, A. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The fertility of nine Typic Dystrandeprs of Costa Rica was studied under laboratory and greenhouse conditions. Chemical soil analysis, retention curves for K, Mg. Mn, Zn, Qu, P, B and S. foliar analysis from sorghum plants grown on unfertilized soils, and a greenhouse test with the missing or additive element technique with sorghum in a liter soil pot, were realized. The methods described by Diaz-Romeu & Hunter for a cualitative soil fertility diagnosis were used. The studied cations present similar nutritional characteristics in the nine Typic Dystrandepts As shown by the greenhouse data, K was the most limiting cation after the P deficiency was corrected It was observed that soil pH and soil bases level are Seul potential fertility indexes for volcanic soils, because Ca and Mg initial contents determine natural fertility In these soils, exchangeable Al was not found important. No Fe problems were observed and the Mn and Zn problems found by soil analysis were not reflected in the greenhouse data Only some soils from the Cordillera de Guanacaste respond positively to Cu application. Ca concentration in 1ypic Dystrudepts of Costa Rica varies, with a 90h statistic probability.rom 32 to 1.7 meg/100 m, Ms, from 0.9 to 3 2 meal100 mi, K, from o03 to 083 meal100 ml, Fe. from 27 to 104 Hg/ml, Mn from traces to 60 H8/ml, Zn, from 14 to 70 Hg/ml and Cu, from traces to 23 4g/ml Soil pH in water varies between 5.6 and 6 7 and in KC between 4.9 and 56 Exchangeable acidity varies from 0 07 to 0 12 meq|100 ml. Ca concentration in foliar tissue of sorghum grown in greenhouse on these soils varies from 0 30 to 0.85%, Ms. from 0 20 to 0.59%, K. from 0 68 to 401%, Fe, from 2to l67 ppm, Mn, from traces to 237 ppm, Zn from 7 to 59 pm, and Cu, from 8 to 26 ppm.